Errores, reniegos e irreverencia : los delitos de palabra y su significado en el tribunal inquisitorial de Cartagena de Indias, 1610-1660 (Editorial Universidad Del Rosario, 2017)
This investigation's interests are the crimes of blasphemy and mistaken propositions perpetrated in the Inquisitorial tribunal of Cartagena between 1610 and 1660. It contextualizes these offences within the general scope of the inquisitorial activities; proposes an interpretative approximation to the meanings these crimes had in their historical context and to the particularities in their prosecution.